Singing Method: Can It Improve the Early Childhoods’ Language Skills? - Hidayat, Rahmat; Tunajijah, Ulfah; Ernasari, Siti; Susanti, Elis; Muhimah, Lulu; Rosmiati, Mia; Nurliani, Lia (CV. Tripe Konsultan, 2024)
Mastering language earlier for early childhoods is very urgent. It is because through language early childhoods can express their thoughts easier to their parents, teachers, and people around them. Through language, early childhoods are also able to learn five other basic abilities, such as: (1) religious and moral values, (2) physical-motor, (3) cognitive, (4) social-emotional, and (5) art. This study aims to analyze the effect of using singing method applied to the early childhoods aged 5-6 years. To acquire the data, the researchers employed qualitative method under a descriptive approach. Based on the observation, the data showed that singing method applied by the teachers at school and also applied by the parents at home become an effective method to enhance the early childhoods’ language skills, such as: (1) helping them to have self-confidence, (2) helping them to be able to memorize the lyrics of the song, (3) helping them to be able to enhance the new vocabulary, and (4) helping them to be able to understand the meaning of the new words. In conclusion, the use of singing method is effective to develop the early childhoods’ language skills.